The Theology of Marriage in Matthew 19:1-12: An Exegetical Response to Marital Instability in Contemporary Christian Communities - Oyeniyi, Oluseye David (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study investigates how Matthew 19:1–12 addresses marital instability in contemporary Christian communities through a text-critical and exegetical approach. While previous scholarship has examined this passage from historical and theological perspectives, limited attention has been given to the integration of textual variant analysis and the syntax of exclusionary clauses within an operational ethical-pastoral framework. The central research question is: How does the syntax and textual variant of the Matthean divorce clause inform a normative Christian ethic of marriage and divorce? Employing the grammatico-historical method, the study utilizes NA28 and UBS5 to examine the variant μὴ ἐπὶ πορνείᾳ (v.9), compares synoptic parallels (Mark 10:2–12; Luke 16:18), and follows a four-stage exegetical process: (1) establishing the critical text, (2) analyzing Greek syntax and semantics, (3) interpreting marital motifs in first-century Jewish and Greco-Roman contexts, and (4) engaging relevant Old Testament intertexts (Genesis 1–2; Deuteronomy 24:1–4). Findings show that Matthew’s exception clause maintains continuity with Jewish legal tradition while reaffirming the covenantal permanence of marriage. Accordingly, the study proposes a pastoral decision matrix that emphasizes covenantal fidelity, ethically conditional divorce, and reconciliation. This exegetically grounded ethic offers practical guidance for church leaders addressing divorce and relational instability amid changing cultural norms.